From the contemporary history of VU Faculty of Mathematics and Informatics: the development of admission to mathematical studies (1991–2024) - Belovas, Igoris (Lietuvos matematikos rinkinys, 2025)
The study examines the trends in student admissions to undergraduate mathematics and informatics programs at the Faculty of Mathematics (1991–1999) and the Faculty of Mathematics and Informatics (1999–2024) of Vilnius University. The review is based on data drawn from primary sources.
Keywords: history of Vilnius University Faculty of Mathematics and Informatics; admission statistics; admission and competition ratios